Coaching the Government Employee with Work Agreements: A Dignified Justice Perspective - Firmansyah, Jaka; Disantara, Fradhana Putra; Ishwara, Ade Sathya Sanathana (Universitas Medan Area, 2024)
The purpose of this study is to evaluate the implementation and identify the development of Government Employees with Work Agreements (PPPK) after the enactment of Law Number 20 of 2023 concerning State Civil Apparatus from the perspective of the theory of dignified justice. This normative legal research uses a legislative and conceptual approach, with primary and secondary legal sources, collected through literature studies and analyzed qualitatively. The results of the study explain that after the enactment of Law Number 20 of 2023 concerning State Civil Apparatus, the development of PPPK has caused various problems, namely unequal perceptions, budget constraints, and the quality of training that still needs to be improved. When this is associated with the theory of dignified justice, this theory encourages ethics and morality as the basis for every aspect of the development, management, and development of PPPK; therefore, by respecting individual dignity, providing equal opportunities, encouraging transparency, and building a positive organizational culture, organizations can ensure that employee development is not only effective, but also fair and dignified. The theory of dignified justice emphasizes that every individual has dignity that must be respected, carrying out performance on an ethical and moral basis that underlies professional behavior. The implementation of these principles will contribute to better employee development and the overall improvement of the quality of public services.